Präsenz durch Verschwinden: Sprache und Ethnizität in der Alltagspraxis junger Kärntner Slowen_innen - Kolb, Jonas (transcript, 2018)
Which part do the ethnics of the Slovenian-speaking inhabitants of Carinthia/Koroska play? This empirical study decodes the mechanisms that constitute the daily lives of the Slovenian residents of Kärnten and contribute to their presence.